New Porcine Model of Arteriovenous Fistula Documents Increased Coronary Blood Flow at the Cost of Brain Perfusion - Valerianova, Anna; Mlcek, Mikulas; Grus, Tomas; Malik, Jan; Kittnar, Otomar (Frontiers in Physiology, 2022)
Background: Arteriovenous fistulas (AVF) represent a low resistant circuit. It is known that their opening leads to decreased systemic vascular resistance, increased cardiac output and other hemodynamic changes. Possible competition of AVF and perfusion of other organs have been observed before, however the specific impact of AVF has not been elucidated yet. Previous animal models studied long-term changes associated with a surgically created high flow AVF. The aim of this study was to create a simple AVF model for the analysis of acute hemodynamic changes. Methods: Domestic female pigs weighing 62.6 ± 5.2 kg were used. All the experiments were held under general anesthesia. The AVF was created using high-diameter ECMO cannulas inserted into femoral artery and vein. Continuous hemodynamic monitoring was performed throughout the protocol. Near-infrared spectroscopy sensors, flow probes and flow wires were inserted to study brain and heart perfusion. Results: AVF blood flow was 2.1 ± 0.5 L/min, which represented around 23 % of cardiac output. We observed increase in cardiac output (from 7.02 ± 2.35 to 9.19 ± 2.99 L/min, p = 0.0001) driven dominantly by increased heart rate, increased pulmonary artery pressure and associated right ventricular work. Coronary artery flow velocity rose. On the contrary, carotid artery flow and brain and muscle tissue oxygenation measured by NIRS decreased significantly. Conclusions: Our new non-surgical AVF model is reproducible and demonstrated an acute decrease of brain and muscle perfusion.